Translation and Validation Study of the Hypoglycemia Fear Survey in a Greek Population of Children and Adolescents with Type 1 Diabetes Mellitus and their Parents - Kostopoulou, Eirini; Andreopoulou, Ourania; Daskalaki, Sophia; Kotanidou, Eleni; Vakka, Angeliki; Galli-Tsinopoulou, Assimina; Spiliotis, Bessie E.; Gonder-Frederick, Linda; Fouzas, Sotirios (Children, 2023)
The present study attempted to translate and culturally adapt an established research instrument, the Hypoglycemia Fear Survey (HFS) questionnaire, to the Greek population and evaluate its validity and internal consistency so that it can be used for the assessment of hypoglycemia fear in Greek children and adolescents with T1DM and their parents. One hundred Greek children and adolescents with T1DM, 54 males, 6–18 years old, and one of their parents participated in this validation study. The participants completed the translated Greek HFS, which includes one version for children (CHFS) and one for parents (PHFS). Exploratory Factor Analysis (EFA) was used to assess construct validity. Internal consistency was assessed using Cronbach’s alpha, and convergent validity was established by estimating the correlation coefficients between the scores of the HFS scales/subscales and the different constructs of the Pediatric Quality of Life Inventory. The CHFS and PHFS exhibited adequate internal consistency for the total score and the Worry subscale, but lower consistency for the Behavior subscale. High test–retest reliability was also shown. We conclude that the Greek version of the HFS is a valid and reliable instrument to assess the fear of hypoglycemia in Greek children and adolescents with T1DM and their parents.
Keywords: HFS validation; fear of hypoglycemia; hypoglycemia; type 1 diabetes mellitus (T1DM)